Nickel-based MOF-derived carbon-based materials and methods and magnesium-sulfur batteries and positive electrode materials

By using nickel-based MOF-derived carbon-based material as the positive electrode material in magnesium-sulfur batteries, the dissolution and anode corrosion problems of magnesium polysulfide are solved, and the cycle stability and discharge specific capacity of the battery are improved.

CN118136799BActive Publication Date: 2025-03-14TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410203514.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-23
Publication Date
2025-03-14
Estimated Expiration
2044-02-23

AI Technical Summary

Technical Problem

The dissolution of soluble magnesium polysulfide in magnesium sulfur batteries leads to the loss of sulfur and capacity attenuation, and the chemical reaction between magnesium polysulfide and the metal magnesium anode leads to anode corrosion and electrolyte consumption, affecting the cyclic stability and discharge specific capacity of the battery.

Method used

Nickel-based MOF-derived carbon-based material is used as the positive electrode material of magnesium-sulfur battery, and nickel-based MOF-derived carbon-based material is prepared by solvothermal method and high-temperature carbonization treatment to form a hollow spherical structure to improve the porosity and active sites of the material.

Benefits of technology

Effectively inhibit the shuttle effect of magnesium polysulfide, promote its rapid conversion, improve the cycle stability and discharge specific capacity of magnesium-sulfur batteries, and improve the charge and discharge performance and circulation performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118136799B_ABST
    Figure CN118136799B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of batteries, and specifically relates to a method for preparing a nickel-based MOF-derived carbon-based material, wherein a transition metal salt is dissolved in an organic solvent, and a nickel-based metal MOF is prepared by a solvothermal method; and then a high-temperature carbonization treatment is performed to obtain a nickel-based metal MOF-derived carbon-based material. In addition, the present invention also provides a nickel-based MOF-derived carbon-based material obtained based on the above-mentioned preparation method. In addition, the present invention also provides the application of the nickel-based MOF-derived carbon-based material in magnesium-sulfur batteries. The present invention utilizes the characteristics of the metal MOF material itself and modifies it with citric acid, so that the structure of its MOF is more loose and porous, and a hollow spherical structure can be formed after high-temperature carbonization; the nickel-based metal MOF-derived carbon-based material is used in the preparation of the positive electrode material of the magnesium-sulfur battery, which can effectively inhibit the shuttle effect of magnesium polysulfide and promote the conversion of magnesium polysulfide, thereby effectively improving the cycle stability and discharge specific capacity of the magnesium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and specifically relates to a nickel-based MOF-derived carbon-based material and method, a magnesium-sulfur battery and a positive electrode material, and more particularly to a nickel-based bimetallic MOF-derived carbon-based material used in a magnesium-sulfur battery positive electrode material and a preparation method. Background Art

[0002] Based on sustainable development strategies, we urgently need to develop high-performance, low-cost green chemical energy sources for the electronic equipment industry. Compared to the poor safety and high price of lithium-sulfur batteries, magnesium-sulfur batteries not only have high volumetric energy density, but also have a high theoretical specific capacity due to the abundance of low-sulfur elements in the Earth's crust.

[0003] However, the dissolution of soluble magnesium polysulfide in magnesium-sulfur batteries can lead to sulfur loss and capacity decay. Furthermore, the chemical reaction between magnesium polysulfide and the metallic magnesium anode can cause anode corrosion and electrolyte consumption. Therefore, how to promote the adsorption of magnesium polysulfide, promote the rapid conversion of magnesium polysulfide, and effectively inhibit the shuttle effect of magnesium polysulfide, thereby effectively improving the cycle stability and discharge specific capacity of magnesium-sulfur batteries, is a question worth studying. Summary of the Invention

[0004] In view of this, the object of the present invention is to provide a nickel-based MOF-derived carbon-based material and method, aiming to overcome the defects existing in the above-mentioned prior art.

[0005] In addition, another object of the present invention is to provide the application of the above-mentioned nickel-based MOF-derived carbon-based material in magnesium-sulfur batteries.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows:

[0007] The preparation method of nickel-based MOF-derived carbon-based materials comprises the following steps:

[0008] Dissolve a transition metal salt, a nickel salt, polyvinyl pyrrolidone, and benzimidazole in a mixed solution of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol, and deionized water, and stir until the solution is clear for later use; wherein the molar ratio of the transition metal atom to the nickel atom is 1:5-1:15;

[0009] While stirring the standby solution, slowly add 0.5-2.0 ml of citric acid to form a configuration solution;

[0010] The prepared solution is placed in a reaction vessel, reacted at a constant temperature of 160-200°C for 12-36 hours, and then filtered to obtain a dark green precipitate. The precipitate is washed with N,N-dimethylformamide multiple times and dried to obtain a nickel-based metal MOF.

[0011] The nickel-based metal MOF obtained above is subjected to a high-temperature carbonization treatment in an inert gas atmosphere to obtain a nickel-based MOF-derived carbon-based material with a hollow spherical structure formed by nanosheet clusters.

[0012] Furthermore, the transition metal salt is any one or more of Fe salt, Co salt, Cu salt, Ag salt, Zn salt, Mn salt, Pt salt, and Cr salt, and the nickel salt is Ni(NO3)2·6H2O or NiCl2·6H2O.

[0013] Furthermore, the mass ratio of the benzimidazole to polyvinylpyrrolidone is 1:10.

[0014] Furthermore, the volume ratio of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol and deionized water is 1:1:1:1.

[0015] Furthermore, the specific process of washing the precipitate with N,N-dimethylformamide multiple times and drying to obtain the nickel-based metal MOF is as follows: first soak the precipitate with N,N-dimethylformamide overnight and then centrifuge it, repeat this process 3-5 times and then dry it, wherein the drying temperature is 80°C and the drying time is 12 hours.

[0016] Preferably, the inert gas is N2, the temperature of the high-temperature carbonization treatment is 600°C, and the time is 150 minutes.

[0017] In addition, the present invention also provides a nickel-based MOF-derived carbon-based material prepared by the above preparation method.

[0018] Specifically, when the transition metal salt used in the above preparation method is a Cu salt, the nickel-based MOF-derived carbon-based material is prepared under the following conditions: the molar ratio of copper atoms to nickel atoms is 1:10, and the content of added citric acid is 1 ml, and the reaction is carried out in a reaction vessel at a constant temperature of 180°C for 24 hours.

[0019] Furthermore, the present invention provides a positive electrode active material for a magnesium-sulfur battery based on the nickel-based MOF-derived carbon-based material prepared above. The positive electrode active material comprises sulfur and a nickel-based MOF-derived carbon-based material, wherein the mass ratio of sulfur to nickel-based MOF-derived carbon-based material is 5:5-6:4.

[0020] Finally, the present invention further provides a magnesium-sulfur battery based on the positive electrode active material obtained above. The magnesium-sulfur battery comprises a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode comprises the positive electrode active material obtained above.

[0021] Beneficial effects of the present invention:

[0022] (1) The present invention utilizes the characteristics of the metal MOF material itself and modifies it with citric acid to make the structure of the MOF more loose and porous and to form a hollow spherical structure after high-temperature carbonization.

[0023] (2) The nickel-based metal MOF-derived carbon-based materials after solvent thermal method and high-temperature carbonization are used to prepare the positive electrode materials of magnesium-sulfur batteries, which can effectively inhibit the shuttle effect of magnesium polysulfide and promote the conversion of magnesium polysulfide, further effectively improving the cycle stability and discharge specific capacity of magnesium-sulfur batteries.

[0024] (3) The preparation process of the present invention is easy to operate and has diverse extension experiments, which provides more ideas for the preparation of positive electrode active materials for magnesium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 The morphologies of Cu@Ni-MOF at different reaction temperatures.

[0027] Figure 2 The morphologies of Cu@Ni-MOF at different reaction times.

[0028] Figure 3 The morphology of Cu@Ni-MOF under different copper-nickel salt ratios.

[0029] Figure 4 The morphology of Cu@Ni-MOF under different citric acid contents.

[0030] Figure 5 These are various morphologies of the bimetallic Cu@Ni-MOF after carbonization, prepared at a constant temperature of 180°C, reaction for 24 hours, addition of 1 mL of citric acid, and a copper-nickel nitrate ratio of 1:10.

[0031] Figure 6 These are the N2 adsorption / desorption curves and pore size distribution curves of Ni-MOF and Cu@Ni-MOF after carbonization.

[0032] Figure 7 This is a comparison chart of the first charge and discharge performance, rate performance and cycle performance of the control group positive electrode material and the magnesium-sulfur battery positive electrode material.

[0033] Figure 8The static adsorption of Ni-MOF and Cu@Ni-MOF on MgS8 solution after carbonization, as well as the UV-visible spectra and XPS spectra of the corresponding supernatant.

[0034] Figure 9 Diagram of the conversion mechanism of polysulfides in magnesium-sulfur batteries. DETAILED DESCRIPTION

[0035] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0036] The dissolution of soluble magnesium polysulfide in magnesium-sulfur batteries leads to sulfur loss and capacity decay. Furthermore, the chemical reaction between magnesium polysulfide and the metallic magnesium anode can cause anode corrosion and electrolyte consumption. Therefore, the present invention aims to address the technical challenges of promoting the adsorption of magnesium polysulfide, accelerating its rapid conversion, and effectively inhibiting its shuttle effect, thereby effectively improving the cycling stability and specific discharge capacity of magnesium-sulfur batteries.

[0037] According to literature records, the charging and discharging principles of magnesium-sulfur batteries are similar to those of lithium-sulfur batteries. The positive electrode material must be a material that can provide reversible embedding / de-embedding channels for metal cations and can alleviate the volume expansion of sulfur. Therefore, some positive electrode active materials in lithium-sulfur batteries can be extended to magnesium-sulfur batteries, including transition metal oxides, sulfides, nitrides, carbon materials and metal-organic framework materials.

[0038] However, metal compounds prepared using traditional methods suitable for lithium-sulfur batteries often have large particle sizes and limited pores, which do not provide sufficient space for volume expansion during charge and discharge. Furthermore, insufficient contact between the metal compound and the active material results in suboptimal Coulombic efficiency and cycling performance in magnesium-sulfur batteries. Therefore, MOFs, with uniformly distributed active sites, high porosity, low density, and large specific surface area, are becoming one of the most suitable materials for magnesium-sulfur battery cathodes.

[0039] MOF is a polymer material that achieves self-assembly by combining metal clusters and organic linkers. By changing the synthesis conditions and the types of metal clusters and organic linkers used, MOF can show greater diversity and controllability, such as catalytic activity and adsorption performance. In addition, MOF can still maintain its pore structure after carbonization at a specific temperature. The carbon skeleton doped with other heteroatoms can improve the transport efficiency of electrons and ions, and the resulting metal compounds can improve the utilization rate and cycle stability of battery active materials. Most importantly, compared with single metal compounds, bimetallic / multimetallic compounds can induce electron transfer between different metals, resulting in changes in electronic structure and reducing the energy barrier of ion and electron migration. Therefore, the method of preparing a variety of metal compounds as positive electrode materials in magnesium-sulfur batteries through metal MOFs has important implications for improving battery cycle stability.

[0040] Therefore, after multiple experimental demonstrations, the technical path of the present invention was finally determined as: utilizing the nucleation rates of different metals and controlling the morphology of MOF by adjusting the ratio of different metal ions; at the same time, utilizing the fact that bimetallic materials have more active sites for redox reactions and the synergistic effect between bimetallic ions, the shuttle effect of magnesium polysulfide can be effectively suppressed, and the discharge specific capacity and cycle stability of magnesium-sulfur batteries can be effectively improved.

[0041] Based on the above technical path, the technical principle of the present invention is determined as follows: a transition metal salt is dissolved in an organic solvent, and a nickel-based metal MOF is prepared by a solvothermal method; then a high-temperature carbonization treatment is performed to obtain a carbon-based material derived from the nickel-based metal MOF; finally, the positive electrode active material and the magnesium-sulfur battery are prepared based on the nickel-based metal MOF-derived carbon-based material.

[0042] According to the above technical principles, the present invention conducted multiple tests on the organic solvent, metal atomic ratio, reaction temperature, reaction time, and carbonization treatment parameters used in the scheme, and finally formed the following technical scheme after repeated optimization.

[0043] The preparation method of nickel-based MOF-derived carbon-based materials comprises the following steps:

[0044] S1. Dissolve the transition metal salt, nickel salt, polyvinyl pyrrolidone, and benzimidazole in a mixture of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol, and deionized water, and stir until the solution is clear.

[0045] The molar ratio of transition metal atoms to nickel atoms is 1:5-1:15; the transition metal salt is any one or two or more of Fe salt, Co salt, Cu salt, Ag salt, Zn salt, Mn salt, Pt salt, and Cr salt, and this application does not impose any restrictions on this; the nickel salt is Ni(NO3)2·6H2O or NiCl2·6H2O, and the preferred nickel salt is Ni(NO3)2·6H2O.

[0046] In addition, the mass ratio of the benzimidazole to polyvinyl pyrrolidone is 1:10; the volume ratio of the N,N-dimethylformamide, ethylene glycol, anhydrous ethanol and deionized water is 1:1:1:1.

[0047] S2. While stirring the standby solution, slowly add 0.5-2.0 ml of citric acid to form a prepared solution. The stirring of the standby solution is preferably magnetic stirring, but this application does not limit this.

[0048] S3. Place the prepared solution into a reaction vessel, react at a constant temperature of 160-200°C for 12-36 hours, and then filter to obtain a dark green precipitate. Wash the precipitate multiple times with N,N-dimethylformamide and dry to obtain a nickel-based metal MOF. In an inert gas atmosphere, perform a high-temperature carbonization treatment on the nickel-based metal MOF obtained above to obtain a nickel-based MOF-derived carbon-based material with a hollow spherical structure composed of nanosheet clusters.

[0049] The specific process of washing the precipitate with N,N-dimethylformamide multiple times and drying to obtain the nickel-based metal MOF is as follows: first soaking the precipitate with N,N-dimethylformamide overnight and then centrifuging it, repeating this process 3-5 times and then drying it, the drying temperature is 80°C, and the drying time is 12 hours.

[0050] In addition, the inert gas is preferably N2, the temperature of the high-temperature carbonization treatment is preferably 600°C, and the carbonization time is preferably 150 minutes.

[0051] Based on the above-mentioned method for preparing nickel-based MOF-derived carbon-based materials, the present invention also provides a nickel-based MOF-derived carbon-based material prepared by the above-mentioned preparation method.

[0052] Furthermore, the present invention provides a positive electrode active material for a magnesium-sulfur battery based on the nickel-based MOF-derived carbon-based material prepared above. The positive electrode active material comprises sulfur and a nickel-based MOF-derived carbon-based material, wherein the mass ratio of sulfur to nickel-based MOF-derived carbon-based material is 5:5-6:4.

[0053] Finally, the present invention further provides a magnesium-sulfur battery based on the positive electrode active material obtained above. The magnesium-sulfur battery comprises a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode comprises the positive electrode active material obtained above.

[0054] It should be noted that the nickel-based MOF-derived carbon-based material can be a nickel-based bimetallic MOF-derived carbon-based material or a nickel-based multimetallic MOF-derived carbon-based material, and this application does not limit this. In the following description of the technical solution, this application mainly uses the nickel-based bimetallic MOF-derived carbon-based material as an example to illustrate its technical principles. The technical principles of the nickel-based multimetallic MOF-derived carbon-based material are similar to those of the bimetallic, so this application does not describe them. At the same time, the positive electrode active material of the magnesium-sulfur battery mentioned in this application has the same meaning as the positive electrode material.

[0055] Next, based on the above-described method for preparing nickel-based MOF-derived carbon-based materials, the present invention takes transition metal Cu salt as an example to elaborate on the fundamental reason for selecting a molar ratio of transition metal atoms to nickel atoms of 1:5-1:15 in the present application scheme.

[0056] Figure 3 The following are the morphologies of Cu@Ni-MOF at different copper-nickel salt ratios. Specifically, (g) shows the morphology of Ni-MOF synthesized with pure nickel salt; (h) shows the morphology of Cu@Ni-MOF synthesized with a copper-nickel molar ratio of 1:5; (i) shows the morphology of Cu@Ni-MOF synthesized with a copper-nickel molar ratio of 1:10; (j) shows the morphology of Cu@Ni-MOF synthesized with a copper-nickel molar ratio of 1:15; and (k) shows the morphology of Cu-MOF synthesized with pure copper salt.

[0057] In (g), the Ni-MOF synthesized by pure nickel salt is a spherical hollow structure composed of nanosheet clusters, but the surface is relatively smooth, which is not conducive to the full contact between the host material and the active substance sulfur; in (h), the Cu@Ni-MOF synthesized when the copper-nickel molar ratio is 1:5 is also a spherical structure composed of nanosheet clusters, but the morphology is too different; in (i), the Cu@Ni-MOF synthesized when the copper-nickel molar ratio is 1:10 is also a spherical structure composed of nanosheet clusters, with basically the same morphology and no block structure; in (j), the Cu@Ni-MOF synthesized when the copper-nickel molar ratio is 1:15 is also a spherical structure composed of nanosheet clusters, but there is an obvious block structure, indicating that the copper molar number is large, Cu-MOF is generated, and the purity is low; in (k), the Cu-MOF synthesized by pure copper salt is a block solid structure with no obvious characteristic morphology.

[0058] Therefore, the optimal molar ratio of metal atoms for the Cu-Ni bimetallic MOF is 1:10.

[0059] Then, based on the above-determined optimal molar ratio of copper to nickel metal atoms of 1:10, the fundamental reason for selecting 0.5-2.0 ml of citric acid in the present application is elaborated in detail.

[0060] Figure 4 The morphologies of Cu@Ni-MOF under different citric acid contents are shown as follows: (l) shows the morphology of Cu@Ni-MOF synthesized without citric acid modification; (m) shows the morphology of Cu@Ni-MOF synthesized after adding 0.5 mL of citric acid modification; (n) shows the morphology of Cu@Ni-MOF synthesized after adding 1 mL of citric acid modification; (o) shows the morphology of Cu@Ni-MOF synthesized after adding 2 mL of citric acid modification.

[0061] In (l), the synthesized spherical Cu@Ni-MOF presents a solid structure with a smooth surface; in (m), the synthesized spherical Cu@Ni-MOF is still solid, but the surface roughness increases; in (n), the synthesized spherical Cu@Ni-MOF clearly presents a hollow structure composed of nanosheet clusters, and the morphology is relatively complete, without obvious "fragment" structure; in (o), although the synthesized spherical Cu@Ni-MOF presents a hollow structure composed of nanosheet clusters, the morphology is severely fragmented and has an obvious "fragment" structure.

[0062] Therefore, the optimal amount of citric acid added to the Cu-Ni bimetallic MOF is 1 mL.

[0063] Next, based on the above-determined conditions of 1 mL of citric acid addition and a copper-nickel metal atomic molar ratio of 1:10, the fundamental reason for selecting a solvothermal reaction temperature of 160-200° C. in the present application is elaborated in detail.

[0064] Figure 1 The following are the morphologies of Cu@Ni-MOF at different reaction temperatures: (a) shows the morphology of Cu@Ni-MOF at a reaction temperature of 160°C; (b) shows the morphology of Cu@Ni-MOF at a reaction temperature of 180°C; and (c) shows the morphology of Cu@Ni-MOF at a reaction temperature of 200°C.

[0065] At 160°C, the synthesized Cu@Ni-MOF formed individual nanosheets. At 180°C, the synthesized Cu@Ni-MOF had a hollow structure. This is primarily because MOF requires external heat to obtain energy to overcome the energy barrier during synthesis. At lower temperatures, there isn't enough energy to ensure further reaction. However, at 200°C, while a hollow Cu@Ni-MOF was synthesized, the high temperature destroyed its morphology.

[0066] Therefore, the optimal synthesis temperature of the solvothermal reaction is 180℃.

[0067] Finally, based on the above-mentioned conditions of the optimal synthesis temperature of the solvothermal reaction of 180°C, the addition amount of citric acid of 1mL, and the molar ratio of copper and nickel metal atoms of 1:10, the fundamental reason for selecting the solvothermal reaction time of 12-36h in this application scheme is elaborated in detail.

[0068] Figure 2 The following are the morphologies of Cu@Ni-MOF at different reaction times: (d) shows the morphology of Cu@Ni-MOF at a reaction time of 12 h; (e) shows the morphology of Cu@Ni-MOF at a reaction time of 24 h; and (f) shows the morphology of Cu@Ni-MOF at a reaction time of 36 h.

[0069] When the reaction time was 12 hours, the hollow structure of Cu@Ni-MOF was successfully synthesized. However, some nanosheets still remained, indicating that when the reaction time is too short, the nanosheets cannot fully cluster into a hollow structure. When the reaction time is 36 hours, the hollowness of the synthesized Cu@Ni-MOF is poor. Therefore, the optimal reaction time is 24 hours.

[0070] In summary, the preparation method of copper-nickel bimetallic MOF for magnesium-sulfur batteries and positive electrode materials is as follows:

[0071] S1. Dissolve a copper salt, a nickel salt, polyvinyl pyrrolidone, and benzimidazole in a mixture of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol, and deionized water, and stir until the solution is clear. The molar ratio of copper atoms to nickel atoms is 1:10; the nickel salt is Ni(NO₃)₂·6H₂O; the mass ratio of benzimidazole to polyvinyl pyrrolidone is 1:10; and the volume ratio of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol, and deionized water is 1:1:1:1.

[0072] S2. While magnetically stirring the standby solution, slowly add 1 ml of citric acid to form a preparation solution.

[0073] S3. The prepared solution was placed in a reaction vessel, reacted at a constant temperature of 180°C for 24 hours, and then filtered to obtain a dark green precipitate. The precipitate was soaked in N,N-dimethylformamide and centrifuged overnight. This process was repeated 3-5 times and then dried at 80°C for 12 hours to obtain a nickel-copper bimetallic MOF, namely Cu@Ni-MOF. The nickel-copper bimetallic MOF obtained above was subjected to high-temperature carbonization treatment in an atmosphere of inert gas N2 at a carbonization temperature of 600°C for 150 minutes to finally obtain a nickel-copper MOF-derived carbon-based material Cu-Cu2O@Ni-NiO@C with a hollow spherical structure composed of nanosheet clusters.

[0074] Below, the present invention takes nickel-copper MOF-derived carbon-based materials as an example to explain in detail how the present invention promotes the adsorption of magnesium polysulfide, how to promote the rapid conversion of magnesium polysulfide, and how to effectively inhibit the shuttle effect of magnesium polysulfide, thereby effectively improving the cycle stability and discharge specific capacity of magnesium-sulfur batteries.

[0075] Figure 5 Shown are various morphologies of bimetallic Cu@Ni-MOF after carbonization prepared at a constant temperature of 180°C, a reaction time of 24 h, the addition of 1 mL of citric acid, and a copper-nickel nitrate ratio of 1:10.

[0076] from Figure 5 As can be seen from the SEM images (A)-5(B), the morphologies of the control Ni-NiO@C and Cu-Cu2O@Ni-NiO@C are both hollow, consistent with the morphologies of the Ni-MOF (g) and the bimetallic Cu@Ni-MOF (i), respectively. These results indicate that annealing does not change the morphology of the samples and that the hollow structures provide ample space for active materials.

[0077] In addition, the cluster structure composed of a large number of nanosheets can effectively increase the contact area with the active material during the charge and discharge process. In addition, by comparing the dark and bright TEM image information, i.e. Figure 5 (C)-5(D), the hollow structure can be similarly proved. The shell of the hollow structure is assembled by a large number of nanosheets, which can increase the contact area between the electrode material and the active material. Figure 5 (E)-5(J) As can be seen from the STEM images and element distribution, the contents of C, O, Ni, Cu, and N in the hollow nanoparticles are lower in the center, confirming the formation of the hollow structure.

[0078] Figure 6 These are the N2 adsorption / desorption curves and pore size distribution curves of Ni-MOF and Cu@Ni-MOF after carbonization.

[0079] Table 1 shows the specific surface area and pore volume of Ni-NiO@C and Cu-Cu2O@Ni-NiO@C

[0080] Table 1

[0081]

[0082] pass Figure 6 The specific surface area and pore characteristics of the samples were calculated from the N2 adsorption and desorption curves shown in (L)-6(M). The specific surface areas of Ni-NiO@C and Cu-Cu2O@Ni-NiO@C are 5.042m 2 g -1 and 11.163m 2 g-1 The pore volumes of Ni-NiO@C and Cu-Cu2O@Ni-NiO@C are 0.021cc g -1 and 0.056cc g -1 It is noteworthy that the specific surface area and pore volume increase significantly after doping with Cu metal nodes.

[0083] Figure 7 This is a comparison chart of the first charge and discharge performance, rate performance and cycle performance of the control group positive electrode material and the magnesium-sulfur battery positive electrode material.

[0084] Figure 7 (N) represents the Ni-NiO@CS and Cu-Cu2O@Ni-NiO@CS at 0.1A g -1 Initial charge and discharge curve under ; Figure 7 (O) shows the initial charge-discharge curves of Cu-Cu2O@Ni-NiO@CS at different current densities; Figure 7 (P) represents the rate performance of Ni-NiO@CS and Cu-Cu2O@Ni-NiO@CS; Figure 7 (Q) represents the Ni-NiO@CS and Cu-Cu2O@Ni-NiO@CS at 0.2Ag -1 Cycling performance under conditions Figure 7 (R) represents the Ni-NiO@CS and Cu-Cu2O@Ni-NiO@CS at 1A g -1 Cycling performance under .

[0085] Table 2 shows the first discharge specific capacity of Ni-NiO@CS and Cu-Cu2O@Ni-NiO@CS at different current densities.

[0086] Table 2

[0087]

[0088] Table 3 shows the cycling performance of Ni-NiO@CS and Cu-Cu2O@Ni-NiO@CS at different current densities.

[0089] Table 3

[0090]

[0091] The initial charge-discharge curves, rate performance and cycle performance of Ni-NiO@CS and Cu-Cu2O@Ni-NiO@CS are shown in Figure 2. Figure 7 As shown. Figure 7(N) It ​​can be seen that the initial discharge capacities of Ni-NiO@CS and Cu-Cu2O@Ni-NiO@CS are 848.6 mAh g -1 and 1050.6mAh g -1 . At the same active material dosage, the Cu-Cu2O@Ni-NiO@CS electrode has a higher discharge specific capacity. This may be due to the excellent catalytic activity of Cu-Cu2O@Ni-NiO, which can promote the conversion of active materials. Electrode materials composed of multimetallic compounds with different oxidation states have been shown to be effective catalysts for several electrochemical catalytic reactions. Similar to other sulfur cathode batteries such as lithium-sulfur batteries, Ni-NiO@CS and Cu-Cu2O@Ni-NiO@CS batteries also exhibit two discharge platforms on the first charge and discharge curve. The first platform is observed at around 1.5V, while the second platform is between 1.0-1.2V. More importantly, the potential difference of Cu-Cu2O@Ni-NiO@CS on the constant current charge and discharge curve is smaller than that of Ni-NiO@CS. When Cu-Cu2O@Ni-NiO@CS is used as the electrode material, the chemical reaction rate within the battery is fast and the internal resistance is low, so a low charge and discharge potential difference can be observed. Compared with Ni-NiO@CS, Figure 7 (O) Cu-Cu2O@Ni-NiO@CS at 0.1Ag -1 , 0.2A g -1 , 0.5Ag -1 , 1Ag -1 and 2Ag -1 The initial discharge capacities were 1050.6 mAh g -1 , 950.6mAh g -1 、890.4mAh g -1 、820.7mAh g -1 and 677.1mAh g -1 At different current densities, Cu-Cu2O@Ni-NiO@CS exhibits more outstanding initial discharge capacity than Ni-NiO@CS.

[0092] Rate performance is used to further demonstrate the integrity of the redox reactions within the electrode materials, e.g. Figure 7(P) is shown. It is worth noting that Cu-Cu2O@Ni-NiO@CS maintains excellent stability at 0.2A g-1, 0.5A g-1, 1A g-1, and 2Ag-1. In particular, when the current density is restored to 0.1A g-1, the discharge capacity still remains at 990.3mAh g-1. The excellent specific capacity recovery rate of 94.28% indicates that the integrity of the internal redox reaction is excellent, which is related to the excellent catalytic performance of the multi-metal oxide. In addition to having a high initial discharge specific capacity and excellent rate performance, Cu-Cu2O@Ni-NiO@CS also has better cycling stability compared with Ni-NiO@CS.

[0093] Figure 7 (Q) represents the Ni-NiO@CS and Cu-Cu2O@Ni-NiO@CS at 0.2A g -1 Cycling performance under conditions Figure 7 (R) represents the Ni-NiO@CS and Cu-Cu2O@Ni-NiO@CS at 1Ag -1 Cycling performance under .

[0094] Due to the high content of active materials in Cu-Cu2O@Ni-NiO@CS, the samples underwent different degrees of activation. After 200 cycles, the specific capacity of Cu-Cu2O@Ni-NiO@CS remained at 914.0 mAh g -1 Compared with Ni-NiO@CS, Cu-Cu2O@Ni-NiO@CS has a good capacity retention rate of 77.07% and a lower capacity decay rate of 0.14%. -1 When the capacity retention rate is 66.89% and the capacity decay rate is 0.06%, the capacity retention rate of Cu-Cu2O@Ni-NiO@CS reaches 88.96% at 100 to 500 cycles, which is significantly higher than that of Ni-NiO@C. The poor cycling stability observed in Ni-NiO@CS can be attributed to its lower specific surface area and smaller contact area with the active material. On the other hand, Cu-Cu2O@Ni-NiO@C has a higher specific surface area and a larger contact area with the active material, resulting in excellent cycling stability. The excellent catalytic activity of Cu-Cu2O@Ni-NiO further enhances the stability. Therefore, Cu-Cu2O@Ni-NiO@CS has excellent cycling stability.

[0095] Figure 8 The static adsorption of Ni-MOF and Cu@Ni-MOF on MgS8 solution after carbonization, as well as the UV-visible spectra and XPS spectra of the corresponding supernatant.

[0096] Static adsorption and UV-visible spectra of Cu-Cu2O@Ni-NiO@C and Ni-NiO@C by MgS8 solution Figure 8 (S) is shown. After 9 hours of static adsorption, the color of the MgS8 solution of the Cu-Cu2O@Ni-NiO@C sample decreased significantly compared to the Ni-NiO@C sample, indicating the effective adsorption of magnesium by polysulfides. In addition, the corresponding UV-visible absorption spectrum shows that the absorption intensity in the visible light range of the MgS8 solution containing the Cu-Cu2O@Ni-NiO@C sample is significantly reduced, indicating that the concentration of MgS8 in the supernatant is low. This result explains the reason for the fading of the MgS8 solution and further confirms that Cu-Cu2O@Ni-NiO@C has a strong adsorption capacity.

[0097] like Figure 8 The C1s fitting spectrum shown in (T) shows peaks at 284.80 eV, 286.41 eV, and 289.72 eV, corresponding to CC / C=C, CO, and NC=O, respectively. It is worth noting that an obvious CS peak at 292.78 eV appears in the C1s spectrum of Cu-Cu2O@Ni-NiO@C, indicating that the N-doped carbon framework can not only physically adsorb polysulfides but also chemically anchor them.

[0098] like Figure 8 As can be seen in the S2p spectrum shown in (U), the presence of Ni-S bond at 163.16eV indicates that nickel in the electrode material can anchor polysulfide through bonding chemistry. The peaks at 168.53eV, 169.26eV, and 170.33eV are polythiosulfate, polysulfide, and thiosulfate, respectively. This further proves that the electrode material can adsorb polysulfide and catalyze its conversion into polythiosulfate and thiosulfate. SO3 at 165.6eV 2- The presence of Cu2O@Ni-NiO@CS is primarily due to surface oxidation. The significant presence of Cu and Cu2S indicates that the presence of Cu-Cu2O in Cu-Cu2O@Ni-NiO@CS enhances the catalytic activity of the electrode material and also strengthens its anchoring effect on the active material. This results in enhanced discharge specific capacity and active material utilization.

[0099] Cu 2p spectroscopy can provide more information on the chemical changes of Cu during cycling. Figure 8 (V) is shown. The XPS spectrum of Cu 2p shows two double spin-orbit peaks at 932.69eV and 952.64eV, which are Cu 2p 3 / 2 and Cu 2p 1 / 2 respectively. The remaining pair of weak peaks are satellite peaks. In addition, Cu 2p 3 / 2 and Cu 2p1 / 2 can be further divided into Cu + 、Cu0 and Cu 2+ .

[0100] By S2p spectrum analysis, it was determined that Cu 2+ The corresponding chemical compositions are Cu2O and Cu, and Cu + The corresponding chemical compositions are Cu2O and Cu2S. Therefore, the hollow structure assembled by the nanosheets has the ability to chemically adsorb and anchor polysulfides. The introduction of Cu not only enhances the capture of intermediates but also accelerates the mutual conversion of polysulfides by participating in redox reactions, thereby improving the utilization of active materials.

[0101] Figure 9 Shown is a diagram of the conversion mechanism of polysulfides in magnesium-sulfur batteries.

[0102] The hollow structure of Cu-Cu2O@Ni-NiO@C provides a spacious storage space for active materials. The distribution of Cu-Cu2O@Ni-NiO on carbon nanosheets exhibits significant catalytic activity and promotes the mutual conversion of polysulfides. In addition, XPS results confirm that the active sites of Cu-Cu2O@Ni-NiO can chemically anchor polysulfides, effectively preventing the shuttle effect and improving the utilization of active materials. In addition, the mutual conversion between copper species enhances the internal reaction kinetics, thereby improving the electrochemical performance. In addition, the nitrogen-doped carbon skeleton ensures efficient conductivity for internal magnesium ion and electron transport. Therefore, the Cu@Ni-MOF-derived carbon-based materials exhibit better cycling stability than other materials, and the stability properties are shown in Table 4.

[0103] Table 4

[0104]

[0105] Finally, based on the technical solutions provided above, the present invention provides the following embodiments:

[0106] Example 1

[0107] Taking the preparation process of Cu-Cu2O@Ni-NiO@C as an example, Ni(NO3)2 and Cu(NO3)2 with a copper-nickel atomic ratio of 1:10 and benzimidazole and polyvinylpyrrolidone with a mass ratio of 1:10 were dissolved in a mixture of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol, and deionized water in a volume ratio of 1:1:1:1. The solution was stirred until clear. Magnetic stirring was then applied, and 1 ml of citric acid was slowly added dropwise while stirring. A solvothermal reaction was carried out at 180°C for 24 hours to obtain a dark green precipitate. The precipitate was washed three times with N,N-dimethylformamide and centrifuged and dried at 80°C for 12 hours to obtain Cu@Ni-MOF. The product was then calcined at 600°C for 150 minutes under a nitrogen atmosphere, followed by natural cooling to room temperature. After carbonization, Cu-Cu2O@Ni-NiO@C was obtained.

[0108] The obtained Cu-Cu2O@Ni-NiO@C and sulfur were manually ground in a mass ratio of 5:5, and then the sulfur was melted by a melting method. The mixture was then mixed with a binder and a conductive agent and coated on a copper foil to prepare a positive electrode sheet. The positive electrode sheet was then assembled into a battery with a magnesium metal sheet and an electrolyte for electrochemical performance testing.

[0109] Figure 5 SEM and TEM images of Cu-Cu2O@Ni-NiO@C show the material's petal-like surface and spherical structure with a hollow center. Citric acid modification loosens the material's structure, providing more active sites. Figure 7 (N) is the magnesium-sulfur battery at 0.1A g -1 The first cycle constant current charge and discharge curve under current density. It can be seen that the first discharge capacity reaches 1050.6mAh g -1 , the battery voltage platform is between 0.9-1.2V. Figure 7 (R) is the current density of 1A g -1 From the cycle curve under current density, it can be seen that after 500 cycles, the capacity retention rate of the magnesium-sulfur battery is 66.89% and the attenuation rate is 0.06%.

[0110] Example 2

[0111] Taking the preparation process of Co-Co2O3@Ni-NiO@C as an example, Ni(NO3)2 and Co(NO3)2 with a cobalt-to-nickel atomic ratio of 1:3 and benzimidazole and polyvinylpyrrolidone with a mass ratio of 1:10 were dissolved in a mixture of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol, and deionized water in a volume ratio of 1:1:1:1. The solution was stirred until clear. Magnetic stirring was then applied, and 1 ml of citric acid was slowly added dropwise while stirring. A solvothermal reaction was carried out at 150°C for 20 hours to obtain a dark green precipitate. The precipitate was washed three times with N,N-dimethylformamide and centrifuged and dried at 80°C for 12 hours to obtain Co@Ni-MOF. The solution was then calcined at 600°C for 150 minutes under a nitrogen atmosphere, then cooled naturally to room temperature. After carbonization, Co-Co2O3@Ni-NiO@C was obtained.

[0112] The obtained Co-Co2O3@Ni-NiO@C and sulfur were manually ground in a mass ratio of 5:5, and then the sulfur was melted by a melting method. The mixture was then mixed with a binder and a conductive agent and coated on a copper foil to prepare a positive electrode sheet. The positive electrode sheet was then assembled into a battery with a magnesium metal sheet and an electrolyte for electrochemical performance testing.

[0113] Co-Co2O3@Ni-NiO@C has the best conductivity when the molar ratio of cobalt and nickel atoms is 1:3. Its morphology is a rough spherical shape with wrinkles on the surface similar to Tremella fuciformis, which is conducive to the rapid diffusion of electrolyte ions. -1 The first discharge capacity at the current density is 902.7 mAh g -1 , the battery discharge platform is between 0.9-1.2V.

[0114] Example 3

[0115] Taking the preparation process of Ag-AgO@Ni-NiO@C as an example, Ni(NO₃)₂ and AgNO₃ (with a silver-nickel atomic molar ratio of 1:8) and benzimidazole and polyvinylpyrrolidone (with a mass ratio of 1:10) were dissolved in a mixture of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol, and deionized water (with a volume ratio of 1:1:1:1) and stirred until the solution became clear. Magnetic stirring was then applied, and 1 ml of citric acid was slowly added dropwise while stirring. A solvothermal reaction was carried out at 160°C for 20 hours to obtain a green precipitate. The precipitate was washed three times with N,N-dimethylformamide and centrifuged, then dried at 80°C for 12 hours to obtain Ag@Ni-MOF. The mixture was then calcined at 600°C for 150 minutes under a nitrogen atmosphere, followed by natural cooling to room temperature. After carbonization, Ag-AgO@Ni-NiO@C was obtained.

[0116] The obtained Ag-AgO@Ni-NiO@C and sulfur were manually ground in a mass ratio of 5:5, and then the sulfur was melted by a melting method. The mixture was then mixed with a binder and a conductive agent and coated on a copper foil to prepare a positive electrode sheet. The positive electrode sheet was then assembled into a battery with a magnesium metal sheet and an electrolyte for electrochemical performance testing.

[0117] The morphology of Ag-AgO@Ni-NiO@C is that Ag nanoparticles are attached to 3D flower-like microspheres. The first discharge capacity of the magnesium-sulfur battery at a current density of 0.1Ag-1 is 980.4mAh g -1 , the battery discharge platform is between 0.9-1.2V.

[0118] Example 4

[0119] Taking the preparation process of Zn-ZnO@Ni-NiO@C as an example, Ni(NO₃)₂ and Zn(NO₃)₂ with a silver-nickel atomic ratio of 1:8 and benzimidazole and polyvinylpyrrolidone with a mass ratio of 1:10 were dissolved in a mixture of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol, and deionized water in a volume ratio of 1:1:1:1. The solution was stirred until clear. Magnetic stirring was then applied, and 1 ml of citric acid was slowly added dropwise while stirring. A solvothermal reaction was carried out at 180°C for 24 hours to produce a light green precipitate. The precipitate was washed three times with N,N-dimethylformamide and centrifuged and dried at 80°C for 12 hours to obtain Zn@Ni-MOF. The solution was then calcined at 600°C for 150 minutes under a nitrogen atmosphere, then cooled naturally to room temperature. After carbonization, Zn-ZnO@Ni-NiO@C was obtained.

[0120] The obtained Zn-ZnO@Ni-NiO@C and sulfur were manually ground in a mass ratio of 5:5, and then the sulfur was melted by a melting method. The mixture was then mixed with a binder and a conductive agent and coated on a copper foil to prepare a positive electrode sheet. The positive electrode sheet was then assembled into a battery with a magnesium metal sheet and an electrolyte for electrochemical performance testing.

[0121] The morphology of Zn-ZnO@Ni-NiO@C is that Zn nanoparticles are adhered to 3D flower-like microspheres. -1 The first discharge capacity at the current density is 902.6 mAh g -1 , the battery discharge platform is between 0.9-1.2V.

[0122] Comparative Example 1

[0123] Taking the preparation of Ni-NiO@C as an example, Ni(NO₃)₂ and a 1:10 mass ratio of benzimidazole and polyvinylpyrrolidone are dissolved in a 1:1:1:1 volume ratio of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol, and deionized water. The solution is stirred until clear. Magnetic stirring is then applied, and 1 ml of citric acid is slowly added dropwise while stirring. A solvothermal reaction is performed at 180°C for 24 hours to produce a light green precipitate. The precipitate is washed three times with N,N-dimethylformamide and centrifuged, then dried at 80°C for 12 hours to obtain Ni-MOF. The product is then calcined at 600°C for 150 minutes under a nitrogen atmosphere, then cooled naturally to room temperature. Carbonization completes the Ni-NiO@C.

[0124] The obtained Ni-NiO@C and sulfur were manually ground in a mass ratio of 5:5, and then the sulfur was melted by a melting method. The mixture was then mixed with a binder and a conductive agent and coated on a copper foil to prepare a positive electrode sheet. The positive electrode sheet was then assembled into a battery with a magnesium metal sheet and an electrolyte for electrochemical performance testing.

[0125] Carbonization at too high a temperature will cause the material structure to collapse, the structure will not be spherical, the petal layer will not be obvious, and it will not provide sufficient active sites. -1 The first discharge capacity at this current density is 848.6 mAh g -1 , the battery discharge platform is between 0.9-1.2V.

[0126] Comparative Example 2

[0127] Taking the preparation process of Cu-Cu2O@Ni-NiO@C-acid-free MOF as an example, Ni(NO3)2 and Cu(NO3)2 with a copper-nickel atomic ratio of 1:10 and a mass ratio of benzimidazole and polyvinylpyrrolidone of 1:10 were dissolved in a 1:1:1:1 mixture of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol, and deionized water. The mixture was stirred until the solution was clear. A solvothermal reaction was performed at 180°C for 24 hours to obtain a dark green precipitate. The precipitate was washed three times with N,N-dimethylformamide and centrifuged, then dried at 80°C for 12 hours to obtain the Cu@Ni-MOF-acid-free MOF. The solid Cu-Cu2O@Ni-NiO@C-acid-free MOF was then calcined at 600°C for 150 minutes under a nitrogen atmosphere and then cooled naturally to room temperature. After carbonization, the solid Cu-Cu2O@Ni-NiO@C-acid-free MOF was obtained.

[0128] The obtained Cu-Cu2O@Ni-NiO@C-acid-free modification and sulfur mass ratio of 5:5 were manually ground and melted by melting method, and then mixed with binder and conductive agent and coated on copper foil to prepare positive electrode sheet, and then assembled into a battery with magnesium metal sheet and electrolyte for electrochemical performance testing.

[0129] From the SEM images, we can find that under the condition of no acid addition, Cu-Cu2O@Ni-NiO@C presents the characteristics of flower-like spheres, but it is not hollow, it is a solid sphere, and the sizes of MOF are different. -1 The first discharge capacity at the current density is 822 mAh g -1 , the battery discharge platform is between 0.9-1.2V.

[0130] Comparative Example 3

[0131] Taking the preparation process of Cu-Cu2O@Ni-NiO@CS-6:4 as an example, Ni(NO3)2 and Cu(NO3)2 with a copper-nickel atomic ratio of 1:10 and benzimidazole and polyvinylpyrrolidone with a mass ratio of 1:10 were dissolved in a mixture of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol, and deionized water in a volume ratio of 1:1:1:1. The solution was stirred until clear. Magnetic stirring was then applied, and 1 mL of citric acid was slowly added dropwise while stirring. A solvothermal reaction was carried out at 180°C for 24 hours to obtain a dark green precipitate. The precipitate was washed three times with N,N-dimethylformamide and centrifuged, then dried at 80°C for 12 hours to obtain Cu@Ni-MOF. The product was then calcined at 600°C for 150 minutes under a nitrogen atmosphere, then cooled naturally to room temperature. After carbonization, Cu-Cu2O@Ni-NiO@CS-6:4 was obtained.

[0132] The obtained Cu-Cu2O@Ni-NiO@CS-6:4 and sulfur mass ratio of 6:4 were manually ground and melted by melting method. Then, it was mixed with binder and conductive agent and coated on copper foil to make positive electrode sheet. The battery was then assembled with magnesium metal sheet and electrolyte for electrochemical performance testing.

[0133] Magnesium sulfur battery at 0.1Ag -1 The first discharge capacity at the current density is 846 mAh g -1 , the battery discharge platform is between 0.9-1.2 V. It can be seen that the ratio of melt-sulfur will greatly affect the capacity of the battery. Selecting the optimal melt-sulfur ratio is also a key step in ensuring the battery has good electrochemical performance.

[0134] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a nickel-based MOF-derived carbon-based material, characterized in that: The following steps are involved: Dissolve a transition metal salt, a nickel salt, polyvinyl pyrrolidone and benzimidazole in a mixed solution of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol and deionized water, and stir until the solution is clear for later use; wherein the transition metal salt is a Cu salt, the nickel salt is Ni(NO3)2·6H2O, and the molar ratio of transition metal atoms to nickel atoms is 1:10; the mass ratio of benzimidazole to polyvinyl pyrrolidone is 1:10; and the volume ratio of N,N-dimethylformamide, ethylene glycol, anhydrous ethanol and deionized water is 1:1:1:1; While the standby solution is stirring, slowly add 1 ml of citric acid to form a configuration solution; The prepared solution was placed in a reaction container, reacted at a constant temperature of 180°C for 24 hours, and then filtered to obtain a dark green precipitate. The precipitate was washed with N,N-dimethylformamide for multiple times and dried to obtain a nickel-based metal MOF. In an inert gas atmosphere, the nickel-based metal MOF obtained above is subjected to a high-temperature carbonization treatment to obtain a nickel-based MOF-derived carbon-based material with a hollow spherical structure formed by nanosheet clusters, wherein the inert gas is N2, the temperature of the high-temperature carbonization treatment is 600°C, and the time is 150 minutes.

2. The method for preparing a nickel-based MOF-derived carbon-based material according to claim 1, characterized in that: The specific process of washing the precipitate with N,N-dimethylformamide multiple times and drying to obtain the nickel-based metal MOF is: first soak the precipitate with N,N-dimethylformamide and centrifuge overnight, repeat this process 3-5 times and then dry it, wherein the drying temperature is 80°C and the drying time is 12 hours.

3. Nickel-based MOF-derived carbon-based material, characterized in that: The preparation method is described in any one of claims 1 to 2.

4. A positive electrode active material for a magnesium-sulfur battery, characterized in that: The positive electrode active material comprises sulfur and the nickel-based MOF-derived carbon-based material according to claim 3, wherein the mass ratio of the sulfur to the nickel-based MOF-derived carbon-based material is 5:5-6:

4.

5. A magnesium-sulfur battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The positive electrode comprises the positive electrode active material according to claim 4.

Citation Information

Patent Citations

  • Preparation method of CoNi bimetal organic framework derived carbon-sulfur composite material

    CN113054183A